Analisis Tematik terhadap Konsep Pendengaran dan Penglihatan: Hearing and Vision in the Qur’anic Epistemology: A Thematic Study of Sam‘and Basar - Syahrial Dinata; Siti Badi'ah; Budimansyah Budimansyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This article examines the epistemological role of hearing (sam‘) and sight (bashar) in the Qur’an using a thematic interpretation approach. The research identifies Qur’anic verses related to sensory perception and analyzes them through classical and contemporary tafsir literature. The findings indicate that hearing frequently appears before sight in Qur’anic discourse, suggesting a structured hierarchy in human cognition. However, modern technological developments have produced a visual-dominant culture where sight tends to be prioritized. The Qur’anic perspective emphasizes the integration of hearing, sight, and the heart as complementary epistemological instruments.